Integrating network pharmacology and multi-omics in a systems approach: a mechanism study of Jinhong tablets against chronic superficial gastritis - Lihao Xiao; Tingyu Zhang; Yun Liu; Chayanis Sutcharitchan; Qingyuan Liu; Xiaoxue Fan; Jian Feng; Huifang Gao; Shao Li; Tong Zhang (Chinese Medicine)
Abstract Background Chronic gastritis (CG) significantly impacts patients’ quality of life and can progress to more severe gastric conditions. In China, Traditional Chinese Medicine (TCM) has been widely applied for its holistic efficacy in treating chronic superficial gastritis (CSG), including formulas like Jinhong Tablets (JHT), known for their anti-inflammatory effects. However, the mechanism of action of JHT in treating CSG still requires further clarification. Purpose This study aimed to elucidate the mechanism by which JHT alleviates CSG, integrating network pharmacology, untargeted metabolomics, and gut microbiota analyses. Methods The CSG rat model was established, and treatment effects were assessed via Hematoxylin and eosin (H&E) staining. The target profiles of JHT’s components and the holistic targets of JHT were obtained. Enrichment analyses were performed on holistic targets and a multi-layer biomolecular network of JHT was established. The study also analyzed rat plasma for differential metabolites through untargeted metabolomics and evaluated the diversity and composition of gut microbiota in fecal and cecal contents samples using 16S rRNA sequencing. Results JHT effectively reduced gastric inflammation in CSG rats. Network pharmacology indicated that diverse metabolic processes including lipid metabolism and nitric oxide metabolism play pivotal roles in the therapeutic effects of JHT on CSG. Metabolomics analysis identified differential metabolites, including betaine, which help enrich the gut microbiota. Phospholipids and citrulline indicate the severity of CSG. The pathway enrichment of differential metabolites confirmed the network pharmacology results and indicated the association with the gut microbiota. Through gut microbiota analyses, it was discovered that JHT could augment the gut microbiota by enhancing the abundance of betaine. Additionally, JHT was shown to boost the production of short-chain fatty acids (SCFAs) by increasing the abundances of Faecalibaculum and Bifidobacterium, consequently alleviating gastric inflammation in CSG. Conclusion Our study revealed that JHT alleviated CSG through diverse metabolic processes including lipid and energy metabolism. Metabolites such as betaine, along with gut microbiota including Faecalibaculum and Bifidobacterium, play crucial roles in the therapeutic interventions. Our findings support the therapeutic potential of JHT and contribute to a deeper understanding of the role of TCM in the treatment of CSG. Graphical Abstract